Landslide Susceptibility Mapping of the Beshisahar-Chame Mountain Road Segment, Nepal Using Geographic Information System and the Analytical Hierarchy Process - Timilsina, Deepak; Joshi, Buddhi Raj; Adhikari, Sundar; Aryal, Rajendra (Journal on Transportation System and Engineering, 2026)
Landslides represent an incessant natural hazard in the mountainous topography of Nepal, where steep slopes, complex geology, intense monsoonal rainfall, and speedily expanding road infrastructure interact to magnify slope instability. This study evaluates anticipated landslide susceptibility along the Beshisahar-Chame mountainous road segment in central Nepal using a geographic information system (GIS) based multi-criteria decision analysis framework. Ten crucial landslide conditioning factors were considered, including slope, aspect, curvature, geology, soil type, land use and land cover, rainfall, drainage density, distance to drainage, and distance to road. The Analytical Hierarchy Process (AHP) was employed to derive relative weights for each factor through pairwise comparisons, confirming consistency of expert judgment. Separate thematic layers were generated from digital elevation models, satellite imagery, published datasets, and landslide inventory in the field, and successively integrated using weighted overlay analysis within a GIS surroundings. The resulting landslide susceptibility map categorises the study area into five zones which are very low, low, moderate, high, and very high susceptibility. Results point that 12.32% of the segment falls within very high susceptibility zones, while 29.23% and 33.55% are considered as high and moderate susceptibility, respectively. Highly susceptible areas are primarily associated with steep, south-facing slopes, weak and fractured lithologies, proximity to roads and drainage networks, and zones of extreme rainfall. The findings spotlight the dominant role of geology, slope gradient, and anthropogenic interventions, particularly unplanned road construction, in prompting landslides. The susceptibility map provides a powerful spatial structure for disaster risk reduction, infrastructure planning, and slope management, aiding informed decision-making for safer road development and sustainable land-use planning in the Himalaya territory.